1998
DOI: 10.3171/jns.1998.88.3.0485
|View full text |Cite
|
Sign up to set email alerts
|

External hydrocephalus after aneurysm surgery: paradoxical response to ventricular shunting

Abstract: The results indicate that for most patients in the SAH group, subdural fluid collection represented "external hydrocephalus" rather than simple "subdural hygroma." Decreased absorption of cerebrospinal fluid because of SAH and surgically created tears in the arachnoid membrane communicating with the subdural space were factors in the development of external hydrocephalus. The authors believe that differentiating external hydrocephalus from subdural hygroma is extremely important, because VP shunt placement can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 12 publications
1
45
0
5
Order By: Relevance
“…Several different terms have been utilized to describe them, including subdural hygromas, external brain tamponade or external hydrocephalus. 15,16,[22][23][24][25] None of these terms appropriately represent the physiologic changes that underlie the development of these collections.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several different terms have been utilized to describe them, including subdural hygromas, external brain tamponade or external hydrocephalus. 15,16,[22][23][24][25] None of these terms appropriately represent the physiologic changes that underlie the development of these collections.…”
Section: Discussionmentioning
confidence: 97%
“…There is no established guideline to define the minimum thickness or volume of these extra-axial collections, so we therefore defined them as fluid collections exerting mass effect, greater than 5 mm in thickness. 22 The appearance of these collections on CT scans had densities consistent with CSF, in order to exclude post-operative hematomas. Resolution of the collections was defined as the time to the first CT scan showing disappearance of the fluid.…”
Section: Methodsmentioning
confidence: 98%
“…PECC is not only a simple fluid accumulation in the extra-axial spaces produced after surgery but due to a fundamental pathological alteration of CSF dynamics and their pathways. Therefore the possible relationship between PECC and poor postoperative clinical outcomes needs special attention [31,32,33,34,35]. The condition is often associated with increased intracranial pressure symptoms which include severe headache and loss of consciousness.…”
Section: Resultsmentioning
confidence: 99%
“…These extra-axial collections have been referred to as subdural hygromas, 8 subdural fluid collections 9 or external hydrocephalus. 10 All of these descriptions have an implied etiological connection to hydrocephalus. Furthermore, some investigators have suggested that post-craniectomy collections should be treated with permanent cerebrospinal fluid (CSF) diversion by shunting, in the same manner that spontaneous subdural hygromas or hydrocephalus are treated.…”
Section: Introductionmentioning
confidence: 97%